2016
DOI: 10.5194/acp-16-4147-2016
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric constraints on the methane emissions from the East Siberian Shelf

Abstract: Abstract. Subsea permafrost and hydrates in the East Siberian Arctic Shelf (ESAS) constitute a substantial carbon pool, and a potentially large source of methane to the atmosphere. Previous studies based on interpolated oceanographic campaigns estimated atmospheric emissions from this area at 8–17 TgCH4 yr−1. Here, we propose insights based on atmospheric observations to evaluate these estimates. The comparison of high-resolution simulations of atmospheric methane mole fractions to continuous methane observati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 34 publications
(54 reference statements)
10
60
1
Order By: Relevance
“…A subsequent measurement campaign led by Thornton et al (2016a), though not made during a stormy period, failed to observe the high rates of continuous emissions reported by Shakhova et al (2014), and instead estimated an average flux of 2.9 TgCH 4 yr −1 . Berchet et al (2016) also found that such values were not supported by atmospheric observations, and instead suggested the range of 0.0-4.5 TgCH 4 yr −1 .…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…A subsequent measurement campaign led by Thornton et al (2016a), though not made during a stormy period, failed to observe the high rates of continuous emissions reported by Shakhova et al (2014), and instead estimated an average flux of 2.9 TgCH 4 yr −1 . Berchet et al (2016) also found that such values were not supported by atmospheric observations, and instead suggested the range of 0.0-4.5 TgCH 4 yr −1 .…”
Section: Introductionmentioning
confidence: 78%
“…Our domain goes from 39 • N to the Pole but it covers all longitudes only above 64 • N, as it is not regular in terms of latitude/longitude. Its regular kilometric resolution of 35 km allows us to avoid numerical issues due to shrunken grid cells near the Pole (Berchet et al, 2016). Twenty-nine vertical levels characterize the troposphere, from the surface to 300 hPa (∼ 9000 m), with an emphasis on the lowest layers.…”
Section: Model Descriptionmentioning
confidence: 99%
See 3 more Smart Citations